Strategi jaringan dalam praktik bertahan hidup perempuan perawat taman di Universitas Sebelas Maret: Network strategies in the survival practices of women garden nurses at Universitas Sebelas Maret - Firli Alfa Riski; Bagas Narendra Parahita; Danang Purwanto (LP2M Universitas Sarjanawiyata Tamansiswa, 2024)
Working for maintenance of the plants requires a high level of focus and a lot of time. The female gardeners are assigned to maintain the beauty of the Sebelas Maret University (UNS) environment. However, there are problems faced by workers both in the work environment and at home. The wages earned are low and only enough to get food needs. Even though there are many shortcomings, the decision to look for another place of work never occurred to workers. Professionalism remains the main vision instilled by workers. The aim of this research was to determine the survival abilities of female gardeners in facing problems and obstacles in their lives. This research uses a qualitative method with a case study approach. Data collection techniques are interviews and sample determination through purposive sampling techniques. The results of this research show the form of survival practices carried out by female gardeners namely by refraining from all desires, earning a double income, and building relationships. Network strategies become the dominant form of survival practice used by workers. Relationships are not only a way for information and a means of assistance, but also as a strengthening medium for them to avoid bad psychological conditions.